Analysis of the Need for Developing Teaching Books on Guidance and Counseling based on Project-Based Learning (PjBL) and Case Studies - Latif, Suciani; Muhammad Fiqri Syahril; Muhammad Amirullah; Salsabila Nasution (Indonesian Journal of Learning Education and Counseling, 2025)
The aim of this research is to analyze the need for developing teaching materials for Guidance and Learning Counseling (BKB) courses based on Project-Based Learning (PjBL) and case studies. This research uses a quantitative approach with a survey method. The research respondents were 188 students from education study programs who took the Guidance and Study Counseling course. Data was collected through a needs questionnaire that measured student assessments of various textbook components and learning methods. The data was analyzed using descriptive quantitative to find the average value for each item/statement regarding the components of the BK Belajar textbook material. The results of the quantitative analysis show that students have a high assessment of components that are relevant to the real world, chapter summaries, practice questions, and multimedia elements such as videos and visuals. Passive learning components such as “effective lectures” were rated low. These findings strongly validate the urgency of developing innovative PjBL-based textbooks and case studies to increase students' understanding, motivation and practical skills, while making a significant contribution to improving the quality of education in the field of guidance and counseling.